Sedentary behavior patterns and bone health among overweight/obesity older women: a cross-sectional study - He, Yixian; Du, Litao; Li, Qingqian; Ren, Xiaoyu; Chen, Si; Pan, Yang (Frontiers in Medicine, 2024)
Background Recent studies have indicated an association between sedentary behavior (SB), particularly patterns of SB, and bone health. However, it remains uncertain how different patterns of SB in overweight/obesity older women impact their bone health. This study aimed to investigate the association between objectively measured SB patterns and bone health in Chinese community-dwelling overweight/obesity older women. Methods Cross-sectional data were obtained from a baseline survey of Physical Activity and Health in Older Women Study. Quantitative ultrasound was used to measure speed of sound (SOS), broadband ultrasound attenuation (BUA), bone quality index (BQI) and T value to evaluate bone health. SB patterns were measured using triaxial accelerometers, including sedentary time in SB bouts of ≥ 10, 30, and 60 min, number of SB bouts ≥ 10, 30, and 60 min. Multiple linear regression was used to examine the associations of different SB patterns with bone health. Results After adjusting for confounders, sedentary time in SB bouts ≥ 60 min, number of SB bouts ≥ 60 min were significantly associated with bone health, with a lower SOS [β = −2.75, 95% confidence interval (CI): −4.96 to −0.53, P = 0.015], BUA (β = −1.20, 95% CI: −2.14 to −0.26, P = 0.013), BQI (β = −1.56, 95% CI: −2.63 to −0.49, P = 0.004), T value (β = −0.08, 95% CI: −0.14 to −0.03, P = 0.004) per 60 min increase of sedentary time in SB bouts ≥ 60 min, and a lower SOS (β = −3.97, 95% CI: −7.54 to −0.40, P = 0.029), BUA (β = −1.80, 95% CI: −3.44 to −0.16, P = 0.031), BQI (β = −2.28, 95% CI: −4.08 to −0.47, P = 0.014) and T value (β = −0.12, 95% CI: −0.22 to −0.03, P = 0.013) per bout increase of SB bouts ≥ 60 min, respectively. Conclusion Limiting the duration of prolonged sedentary bouts and minimizing the occurrence of number of SB bouts ≥ 60 min could be essential in bone health management, especially for those older people who are overweight/obesity.